Does pelvic congestion syndrome influence symptoms of chronic venous disease of the lower extremities?. (December 2019) - Gavrilov, S.G.; Moskalenko, Ye.P.
Abstract: Objective: The study was aimed at assessing the influence of pelvic congestion syndrome (PCS) on the clinical manifestations of chronic venous disease (CVD) of the lower extremities in patients with concomitant varicose veins of the pelvis and lower extremities. Study Design: We examined clinically and with duplex ultrasound 30 women with varicose veins of the lower extremity only (VVLE) and another 45 women with VVLE and concomitant varicose veins of the pelvis (VVP) causing symptoms of the pelvic congestion syndrome (PCS). All patients had chronic venous disease (CVD) of class C2 (n = 47) or C3 (n = 28) according to the CEAP classification. All patients underwent duplex ultrasound (DUS) of the lower extremities and pelvis. Based on the clinical examination and DUS findings, the patients were allocated into two groups: group 1 (n = 30 patients with isolated VVLE without the signs of PCS and pelvic veins lesions) and group 2 (n = 45 patients with concomitant PCS, VVP and VVLE). The rates and severity of varicose, pain, and edema syndromes, and leg heaviness were assessed. Results: The patients of the group 2 had significantly more severe clinical manifestations of CVD, 4 times higher risk of leg pain (odds ratio [OR] 4.23; 95% CI 1.57–11.39), 7 times higher risk of leg edema (OR 7.42; 95% CI 2.23–24.78), 5 times higher risk of leg heaviness (OR 5.3; 95% CI 1.85–15.07), and in general 2 times more severe varicose veins, compared with the group 1. Conclusion: The PCS is associated with an increase in the incidence and severity of the CVD symptoms.